A Prospective Comparative Study of Clavipectoral Fascial Plane Block versus Interscalene Block for Postoperative Analgesia in Elective Clavicle Surgeries - Dr. P. G. Raghavendra, Dr. Sahana P R, Dr. Asif (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Clavicle fractures commonly require surgical fixation, and optimal perioperativeanalgesia is essential for patient satisfaction and recovery. Traditionally, the interscalene block (ISB) has been preferred